(w+3)7=-7

Simple and best practice solution for (w+3)7=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (w+3)7=-7 equation:


Simplifying
(w + 3) * 7 = -7

Reorder the terms:
(3 + w) * 7 = -7

Reorder the terms for easier multiplication:
7(3 + w) = -7
(3 * 7 + w * 7) = -7
(21 + 7w) = -7

Solving
21 + 7w = -7

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-21' to each side of the equation.
21 + -21 + 7w = -7 + -21

Combine like terms: 21 + -21 = 0
0 + 7w = -7 + -21
7w = -7 + -21

Combine like terms: -7 + -21 = -28
7w = -28

Divide each side by '7'.
w = -4

Simplifying
w = -4

See similar equations:

| 0=x^2-14x+49 | | 13=m | | 3(x-2)=12x | | 9y-8-5y=5y-5 | | [3t-2]+6=2 | | -9+5x+2=48 | | 1.5t=-9 | | 8=12y+6x | | .6w=.48 | | 4(m+6)=4 | | 3x-12+3=33 | | 63=9m | | 2h+4h-9h=h | | a-11=-18 | | 10x-4x-2-1=15 | | 4[1-(-6x-2)]=120x+44 | | 4[1-(6x-2)]=120x+44 | | 5x-(2x-1)=10+2(3-x) | | 3x^2-5=34 | | -.4=g-4.9 | | -5x-6+9x=34 | | 2x^2+3+5x=0 | | 5(b-6)=90 | | -5(x+9)-7=-52 | | 4x^2+5y^2-20=0 | | 6(3y-7)=56 | | 176576=2x+29888 | | 4x+4y+2-2y-7x-6= | | 13y-11y=8 | | x^2+3+5x=0 | | 7x^2-16x+100=0 | | 8y-25=13-11y |

Equations solver categories